Investigating the zoonotic origin of the West African Ebola epidemic - Marí Saéz, Almudena; Weiss, Sabrina; Nowak, Kathrin; Lapeyre, Vincent; Zimmermann, Fee; Düx, Ariane; Kühl, Hjalmar S; Kaba, Moussa; Regnaut, Sebastien; Merkel, Kevin; Sachse, Andreas; Thiesen, Ulla; et al. (EMBO molecular medicine, 2015)
The severe Ebola virus disease epidemic occurring in West Africa stems from a single zoonotic transmission event to a 2‐year‐old boy in Meliandou, Guinea. We investigated the zoonotic origins of the epidemic using wildlife surveys, interviews, and molecular analyses of bat and environmental samples. We found no evidence for a concurrent outbreak in larger wildlife. Exposure to fruit bats is common in the region, but the index case may have been infected by playing in a hollow tree housing a colony of insectivorous free‐tailed bats ( Mops condylurus ). Bats in this family have previously been discussed as potential sources for Ebola virus outbreaks, and experimental data have shown that this species can survive experimental infection. These analyses expand the range of possible Ebola virus sources to include insectivorous bats and reiterate the importance of broader sampling efforts for understanding Ebola virus ecology. Synopsis The severe Ebola virus disease epidemic occurring in West Africa likely stems from a single zoonotic transmission event involving a 2‐year‐old boy in Meliandou, Guinea, who might have been infected by hunting or playing with insectivorous free‐tailed bats living in a nearby hollow tree. Monitoring data show that larger wildlife did not experience a recent decline and is therefore unlikely to have served as the source for the Ebola virus disease epidemic in West Africa. Fruit bat hunting and butchering are common activities in southern Guinea, therefore facilitating direct human contact. Children are also exposed to insectivorous bats through hunting in and around villages. No large colony of fruit bats exists in or nearby the index village (Meliandou). The 2‐year‐old index case may have been infected by playing in a hollow tree housing a colony of insectivorous free‐tailed bats ( Mops condylurus ). Graphical Abstract The severe Ebola virus disease epidemic occurring in West Africa likely stems from a single zoonotic transmission event involving a 2‐year‐old boy in Meliandou, Guinea, who might have been infected by hunting or playing with insectivorous free‐tailed bats living in a nearby hollow tree.